2013
DOI: 10.1016/j.humimm.2013.08.269
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of regulatory T cell (Treg) function in patients infected with Leishmania braziliensis

Abstract: Th1 immune responses are crucial for eliminating Leishmania parasites. However, despite strong Th1 responses, cutaneous leishmaniasis (CL) patients infected with L. braziliensis develop the disease, while milder Th1 responses are found in sub-clinical (SC) infections. Therefore, CL patients may experience impaired regulatory T cell (Treg) function, causing excessive Th1 responses and tissue damage. To address this hypothesis, we characterized the function of circulating Tregs in L. braziliensis infected CL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…In patient studies of L. V. panamensis , Treg functionality was diminished during infection but was restored following successful treatment (28). Tregs with varying functionality (with suppressive or non-functional properties) have been identified in lesions of patients infected with L. (V.) braziliensis (24, 25). In contrast for L. (V.) guyanensis (35), although FoxP3 and IDO expression in lesions decrease during disease, higher levels are found for patients with chronic disease, suggesting a role for Tregs in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In patient studies of L. V. panamensis , Treg functionality was diminished during infection but was restored following successful treatment (28). Tregs with varying functionality (with suppressive or non-functional properties) have been identified in lesions of patients infected with L. (V.) braziliensis (24, 25). In contrast for L. (V.) guyanensis (35), although FoxP3 and IDO expression in lesions decrease during disease, higher levels are found for patients with chronic disease, suggesting a role for Tregs in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the suppressor activity of Tregs, CD4 + CD25 + T cells (1 × 10 5 cells/well) were first activated as previously described . For Immunosuppression assay, the total PBMC from autologus individuals were stained with CFSE and cultured alone or in presence of CD4 + CD25 + T cells (1 × 10 4 cells/well) with or without 1 μg/ml PHA .…”
Section: Methodsmentioning
confidence: 99%
“…For each sample, CFSE dilution was evaluated in PHA‐stimulated cultures, in the presence or absence of different amounts of purified CD4 + CD25 + cells. T‐cells proliferation was characterized by sequential halving of CFSE fluorescence, generating equally spaced peaks on a logarithmic scale . Data represent the percentage of inhibition calculated on the PHA‐induced proliferation of allogeneic T cells cultured with PHA in the absence of CD4 + CD25 + T cells.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it could be argued that the effects of the IL2RA variants on CL susceptibility are unrelated to their effects on Treg cells. Previous studies (33,34) have suggested that Treg cells may aggravate L. braziliensis infections. In the Brazilian replication study, rs10905669 did not reach the significance threshold and was not included in the analysis.…”
Section: Foxp3mentioning
confidence: 95%